Modification and Testing of Wind Turbine with Double Savonius - Yunus, A. M. Shiddiq; Wahdah, Adhe (Politeknik Negeri Ujung Pandang, 2016)
Indonesia geographically located at tropical region where the wind is very fluctuate and relatively slow. Therefore it is important for designer to investigate the proper design of the slow wind speed turbine that applicable in Indonesia. In this paper, Savonius wind turbine is selected and modified with double level to explore its capability in generating voltage. The main aim of this study is to investigate the performance of the double Savonius turbine in term of its capability in generating voltage. In experimental test, it can be obtained that the double Savonius Turbine could effectively generate 12V at 3 m/s and 17V at 5.4 m/s.